How to provide scientific advice for ecosystem‐based management now. Issue 2 (21st December 2017) - Trenkel, Verena M
Abstract: In this paper, I argue that we have at hand what is needed to provide scientific advice for ecosystem‐based management of small pelagics and other species groups now. The ingredients for this advice are (i) large marine ecosystems as spatial management units; (ii) maintaining ecosystem productivity and exploiting at multispecies maximum yield as overarching management objectives; (iii) assessment of ecosystems by evaluating changes in primary productivity; (iv) an operational management procedure in which single‐species catch proposals are adjusted to ecosystem productivity using a set of control rules. Inspection of historic landings for small pelagics and other small species in the Northeast Atlantic (ICES area) reveals that most likely fisheries exploitation does not, and never did, exceed system productivity in most LMEs and is therefore overall sustainable, although not necessarily for individual stocks.